Evaluasi Pengadaan Obat Publik Pada JKN Berdasarkan Data e-Catalogue Tahun 2014-2015 - Dwiaji, Ary; Sarnianto, Prih; Thabrany, Hasbullah (Jurnal Ekonomi Kesehatan Indonesia, 2016)
Since National Health Insurance (JKN) has been implemented, drug procurement in public health care facilities use e-Purchasing via e-Catalogue. Based on the RKO and HPS, drafting e-Catalogue have gone through a tender process and price negotiations. The process chain will effect the type (molecules) and the amount of drug through the e-Catalogue as well as the number and volume of demand by public health care facilities (e-Order).